2015
DOI: 10.1017/ice.2015.245
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Barrier Injury Laboratory-Confirmed Bloodstream Infections (MBI-LCBI): Descriptive Analysis of Data Reported to National Healthcare Safety Network (NHSN), 2013

Abstract: OBJECTIVES To determine the impact of mucosal barrier injury laboratory-confirmed bloodstream infections (MBI-LCBIs) on central-line-associated bloodstream infection (CLABSI) rates during the first year of MBI-LCBI reporting to the National Healthcare Safety Network (NHSN) DESIGN Descriptive analysis of 2013 NHSN data SETTING Selected inpatient locations in acute care hospitals METHODS A descriptive analysis of MBI-LCBI cases was performed. CLABSI rates per 1,000 central-line days were calculated with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 13 publications
(22 reference statements)
4
35
0
5
Order By: Relevance
“…11 The recognition that the dogma "BSIs are CL-associated unless proven otherwise" was not a good fit for specialty populations (eg, PHO patients) led to defining a new category of MBI-LCBI in January 2013 16 and to plans for removing those infections from the CLABSI category. When MBI-LCBIs are no longer counted as CLABSIs, the CLABSI rate in PHO patients will, based on our data and similar results by others, [16][17][18][19] drop by at least 50%. This decrease may remove CLABSIs from the spotlight, but it makes them no less clinically meaningful or important to prevent.…”
Section: Discussionsupporting
confidence: 88%
“…11 The recognition that the dogma "BSIs are CL-associated unless proven otherwise" was not a good fit for specialty populations (eg, PHO patients) led to defining a new category of MBI-LCBI in January 2013 16 and to plans for removing those infections from the CLABSI category. When MBI-LCBIs are no longer counted as CLABSIs, the CLABSI rate in PHO patients will, based on our data and similar results by others, [16][17][18][19] drop by at least 50%. This decrease may remove CLABSIs from the spotlight, but it makes them no less clinically meaningful or important to prevent.…”
Section: Discussionsupporting
confidence: 88%
“…Although in pediatric oncology critical care locations reductions in CLABSI rates appear to be more modest, few events overall were reported in this location type making comparisons limited. These findings are largely consistent with what was seen from optional CLABSI reporting [2]. This analysis does not directly address potential differences in patient mix among a single NHSN location type, though the MBI-LCBI definition is likely to be of benefit when such differences are related to the presence of oncology patients in some locations and not others.…”
Section: Discussionsupporting
confidence: 74%
“…The MBI LCBI definition was developed to enable surveillance staff in hospitals to identify and report bloodstream infections in oncology patients that likely were the result of mucosal barrier injury and therefore not preventable through recommended central line insertion and maintenance practices [1]. Analysis of the first year of MBI-LCBI data reported to NHSN suggested that excluding MBI-LCBI events from central line-associated bloodstream infection (CLABSI) rates would result in large (>40%) overall reductions in CLABSI rates from inpatient oncology locations but would only reduce CLABSI rates modestly nationwide [2]. However, reporting whether CLABSIs fulfilled the MBI-LCBI criteria during 2013 was an optional part of the CLABSI protocol [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This distinction may contribute to further reduction in true CLABSI rates in this population 15,[142][143][144] and may provide an opportunity for identification of risk factors specific to MBI-LCBI in HCT patients, enabling more targeted prevention strategies, distinct from current CLABSI prevention strategies. Abbreviations: BSI = bloodstream infection; CLABSI = central line-associated bloodstream infection; ICU = intensive care unit; IQR = interquartile range; MBI-LCBI = mucosal barrier injury laboratory-confirmed bloodstream infection.…”
Section: Bloodstream Infection Preventionmentioning
confidence: 99%